Fully homomorphic encryption scheme from RLWE - Dian-hua TANG; Shi-xiong ZHU; Lin WANG; Hao-miao YANG; Jia FAN (Tongxin xuebao)
Based on the somewhat homomorphic scheme of Kristin Lauter et al.a new technique,called Relinearization with key switching was presented.Combining this technique with modulus switching,a (leveled) fully homomorphic encryption scheme without bootstrapping from RLWE were designed.Homomorphic operations of this scheme is simple,and trivial gate operation given in the scheme can make level structure of circuit clearer.Finally,bootstrapping was used as optimization to evaluate capability of the proposed scheme.